From War on Terror to Taliban Resurgence: Pakistan’s Strategic Objectives in Afghanistan (2001–2021) - Muhammad Saqib Gulzar; Dr. Shahzad Akhtar (Corresponding Author) (`, 2025)
This paper evaluates Pakistan’s strategic interest in Afghanistan following the events of 9/11, 2001 by analyzing how Pakistan’s regional security calculus evolved over time. This study is rooted in the theoretical premises of Realism, Security Dilemma and Strategic Depth. It examines the continuity and transformation of the Pakistan’s Afghan Policy with regards to changing global and regional trends. Through a qualitative and analytical method, this paper integrates the historical evidence and contemporary developments to evaluate the strategic behaviour, diplomatic choices, and policy changes of Pakistan during 20 years of intervention and negotiation. The findings suggest that the rationale behind Pakistan’s strategies were driven by classical realism, the needs of state survival, regional equilibrium, and to pursue relative power within an anarchic system. The two-fold strategy of collaboration with the United States in the War on Terror while preserving the relationships with the Taliban illustrates the efforts of Pakistan in balancing the external and internal strategies of self-reliance and state survival. The continued Security Dilemma with India coupled with the wavering alliances of Afghanistan put Pakistan in a loop of defence mechanisms which are perceived as offensive, by its neighbours, and which has driven the regional mistrust further- a central feature of realist power politics. The discussion highlights the development of the Strategic Depth doctrine of Pakistan, which has evolved from militarized intervention to a diplomatic intervention, for example, Pakistan’s facilitative role in the 2020 Doha Agreement. However, the Taliban revival of 2021 highlighted the weaknesses of state-centric approaches to security and the inadequacy of the role of Pakistan. To achieve the lasting stability in Pakistan, it must transcend zero-sum paradigms not through dominance, but through economic interdependence, cooperative security, and political dialogue. Keywords: Strategic Depth, Realism, Security Dilemma, Taliban, Post-9/11 Policy, Regional Security